Association between early worsening of kidney function and poor outcomes in patients treated with renin angiotensin system inhibitors: A meta‐analysis. Issue 10 (28th June 2021) - Yuan, Shizhu; Liu, Yueming; He, Wenfang; Jin, Juan; Liu, Lin; He, Qiang
Abstract: Aim: As renin angiotensin system inhibitors (RASi) are widely used in the clinic, early worsening of kidney function (EWKF) after RASi therapy deserves attention, as its clinical significance is unknown. The aim was to evaluate the relationship between EWKF and long‐term outcomes including all‐cause mortality, kidney and cardiovascular events, in all the patients treated with RASi. Methods: We searched PubMed, Embase, and the Cochrane databases for controlled trials that compared the outcomes of patients with and without EWKF after RASi treatment. Our primary outcome was all‐cause mortality, and secondary outcomes were kidney and cardiovascular events. We pooled data using a random effects model. Results: A total of ten studies were enrolled, of which eight were randomized trials (including 33 454 patients) and two were observational studies (including 148 144 patients). Of the eight randomized trials, 4996 patients with type 2 diabetes, 19 118 with heart failure (HF), and 9340 with atherosclerotic vascular disease and diabetes with end‐organ damage. Both observational studies investigated all kinds of patients with initial RASi treatment. In patients with RASi, the EWKF group had a higher risk of all‐cause mortality than the no‐EWKF group in the randomized studies (n =  13 581; RR, 1.22; 95% CI, 1.04–1.42; P  = .02) and in observational studies (n = 148 144; OR, 1.70; 95% CI, 1.43–2.01; P  < .00001). In patients who experienced EWKF, no statistically significant difference was found between the efficacy of RASi and placebo in all‐cause mortality (n = 1762; RR, 0.85; 95% CI, 0.68–1.06; P  = .14). Conclusion: RASi treatment led to an increased incidence of EWKF which was associated with poorer long‐term outcomes. As the benefit of RAS blockade to patients with EWKF was limited, we suggest clinicians use RASi with caution when EWKF occurs. SUMMARY AT A GLANCE: Blockade of the renin‐angiotensin system (RAS) is best practise first line therapy for a majority of chronic kidney diseases, especially diabetic kidney disease. This systematic review argues that RAS blockade is associated with early worsening of kidney function and poorer prognosis.